Nonverbal Communication in Text-Based, Asynchronous Online Education - Al Tawil, Rima (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
Does nonverbal communication exist in asynchronous, text-based online education? It is commonly believed that it does not due to the absence of body language and paralanguage. An examination of the definitions and forms of nonverbal cues suggests the possibility for some of them to be transmitted through asynchronous, text-based online human interactions. To explore the presence, type, and potential impact of electronic nonverbal cues (eNVC), I conducted this research using the Exploratory Sequential Mixed-Method Design. Phase 1 constituted the preliminary, qualitative stage of this research, during which participants completed an online questionnaire to identify what actions, if any, could speak louder than words in discussion-based courses. Thematic analysis of the questionnaire answers revealed the potential existence and influence of several eNVC categories. Phase 2 constituted the quantitative stage, and served to validate Phase 1 findings through the data collection and analysis of two versions of an online survey: one for professors and another for learners. The collated research findings confirmed that eNVC exist and communicate messages beyond those sent and received through printed words in the asynchronous, online learning environment. According to study participants, these types of electronic cues contributed to the social and teaching presences, and therefore carried the potential to influence students’ levels of engagement and motivation.